On asymptotical behavior of solution of Riccati equation arising in linear filtering with shifted noises - Bashirov, Agamirza E.; Mazhar, Zeka (Springer, 2007)
In this paper we consider a linear signal system together with the two linear observation systems. The observation systems differ from each other by the noise processes. The noise of one of them is a constant shift in time of the signal noise. In the other one the shift is neglected. Respectively, we consider two best estimates of the signal corresponding to two different observation systems. The following problem is investigated: whether the effect of the shift on the best estimate becomes negligible as time increases. This leads to a comparison of the asymptotical behaviors of the solutions of respective Riccati equations. It is proved that under a certain relation between the parameters, the effect of the shift is not negligible
Keywords: Asymptotical Behavior; Solution Of Riccati; Equation Arising; Linear Filtering; Shifted Noises